2006
DOI: 10.1021/ic0602953
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Vanadyl (VO2+) with Ligands Containing Serine, Tyrosine, and Threonine

Abstract: Reaction of vanadyl sulfate with an aldehyde (2-hydroxy-1-naphthaldehyde (nap); 3-methoxysalicylaldehyde = o-vanillin (van)) and an amino acid carrying an OH group (L-tyrosine (L-tyr); L-serine (L-ser), L-threonine (L-thr)) yielded the complexes [VO(nap-D-Tyr)(H2O)] 1a, [VO(van-D,L-Tyr)(H2O)] 1c, [VO(nap-Ser)(H2O)] 2a, [VO(van-D,L-Ser)(H2O)] 2b, [VO(nap-Thr)(H2O)] 3a, and [VO(van-Thr)(H2O)] 3b. [VO(nap-L-tyr(H2O)], 1b, was obtained from the reaction between [VO(nap)(2)] and l-TyrOMe. The crystal and molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…34 In this work, HRNap was obtained in high yield (94%), following a simpler method reported by Chow and Ebel. 36,37 Typically, an amino acid Schiff base with an o-hydroxyaryl moiety enables its isolation due to intramolecular stabilization by hydrogen bonding. 34 As an attempt to elucidate the effect of para-substituent to -OH of hydroxyaryl, nitro and methyl are chosen as electron withdrawing and donating groups respectively.…”
Section: Resultsmentioning
confidence: 99%
“…34 In this work, HRNap was obtained in high yield (94%), following a simpler method reported by Chow and Ebel. 36,37 Typically, an amino acid Schiff base with an o-hydroxyaryl moiety enables its isolation due to intramolecular stabilization by hydrogen bonding. 34 As an attempt to elucidate the effect of para-substituent to -OH of hydroxyaryl, nitro and methyl are chosen as electron withdrawing and donating groups respectively.…”
Section: Resultsmentioning
confidence: 99%
“…ENDOR reveals that, at the low-affinity site, the divalent metal ion is exclusively in an oxygen-functional coordination sphere. 91 In any case, the role of vanadate as an oxidation catalyst is in accord with its common use in oxidation processes not related to biochemical events. If the myosin subfragment 1 is irradiated with UV light in the presence of vanadates, cleavage occurs and vanadate is reduced to vanadyl, which is not active as an energy transmitter in photo-cleavage.…”
Section: Nonfunctional Binding Of Vanadate and Vanadyl To Proteinsmentioning
confidence: 97%
“…The second ligand in this study, Na 2 YNap, was prepared similarly to that reported by Rehder and co-workers, but with no esterification of the carboxylate group. 34 Complexation of these Schiff bases with M (II) (M ¼ Ni, Cu) is shown in Scheme 1. The Ni(II) complex 3 was prepared in a one-pot reaction in which the ligand was formed in situ.…”
Section: Synthesesmentioning
confidence: 99%